2019
DOI: 10.1159/000497125
|View full text |Cite
|
Sign up to set email alerts
|

Strength of Fibroblast Growth Factor 23 as a Cardiovascular Risk Predictor in Chronic Kidney Disease Weaken by ProBNP Adjustment

Abstract: Background: Various epidemiological studies linked high fibroblast growth factor 23 (FGF23) levels with cardiovascular events in chronic kidney disease (CKD). It remains enigmatic whether high FGF23 exerts adverse cardiovascular effects, or whether it reflects detrimental effects of residual confounders. Earlier studies adjusted for CKD-mineral bone disease (CKD-MBD) regulators of FGF23 rather than for recently discovered non-CKD-MBD regulators, among which iron deficiency and heart failure are of particular i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Hence, the present data are in contrast to some of the previously published cohort studies which suggested a strong and independent association with all‐cause mortality, cardiovascular mortality, or need for hospitalization even after adjustment for (NT‐pro) BNP. Our data are, however, in line with the CARE FOR HOMe study that initially showed a strong association between FGF23 and the development of HF in patients with chronic kidney disease, but this association was lost when adjusting for NT‐proBNP …”
Section: Discussionsupporting
confidence: 89%
“…Hence, the present data are in contrast to some of the previously published cohort studies which suggested a strong and independent association with all‐cause mortality, cardiovascular mortality, or need for hospitalization even after adjustment for (NT‐pro) BNP. Our data are, however, in line with the CARE FOR HOMe study that initially showed a strong association between FGF23 and the development of HF in patients with chronic kidney disease, but this association was lost when adjusting for NT‐proBNP …”
Section: Discussionsupporting
confidence: 89%
“…Besides, cFGF23 is more consistently associated with outcome as shown in the meta-analysis of Xiao et al in which c-term FGF23 was associated with mortality in HD patients whereas iFGF23 measurement did not correlate to mortality [40]. Furthermore cFGF23 is a better predictor for identifying patients with declining renal function [41], atherosclerosis associated cardiovascular disease and heart failure [42]. Therefore, the cFGF23 assay may outperform the iFGF23 assay for clinical use, especially for the purpose of patients individuals risk assessment.…”
Section: Using Intact or C-terminal Fgf23 Assay And When?mentioning
confidence: 95%
“…However, other studies showed no improvement at all [42,54]. Interestingly the study by Emrich et al found that when NT proBNP was added to the model the predictive value of FGF23 was largely eliminated and NT proBNP had a much stronger discriminating ability than FGF23 [42]. Overall, FGF23 only marginally improved the prediction for outcome.…”
Section: Fgf23 As a Risk Predictormentioning
confidence: 98%
See 1 more Smart Citation
“…According to meta-analysis of Xiao et al, C-terminal but not intact FGF23 was significantly associated with all-cause mortality risk [ 39 ]. Moreover, cFGF23 is considered a better predictor of CKD progression and atherosclerosis associated with cardiovascular diseases (CVD) and heart failure (HF) [ 40 , 41 ]. Thus, the cFGF23 assay may be a better choice for clinical use, especially regarding individual risk assessment.…”
Section: Measurement Of Fgf23mentioning
confidence: 99%